Disentangling common and specific neural subprocesses of response inhibition - Sebastian, Alexandra; Pohl, M. F.; Klöppel, S.; Feige, B.; Lange, T.; Stahl, C.; Voß, Andreas; Klauer, K. C.; Lieb, K.; Tüscher, O. (NeuroImage, 2013)
Response inhibition is disturbed in several disorders sharing impulse control deficits as a core symptom. Since response inhibition is a cognitively and neurally multifaceted function which has been shown to rely on differing neural subprocesses and neurotransmitter systems, further differentiation to define neurophysiological endophenotypes is essential. Response inhibition may involve at least three separable cognitive subcomponents, i.e. interference inhibition, action withholding, and action cancelation. Here, we introduce a novel paradigm - the Hybrid Response Inhibition task - to disentangle interference inhibition, action withholding and action cancelation and their neural subprocesses within one task setting during functional magnetic resonance imaging (fMRI). To validate the novel task, results were compared to a battery of separate, standard response inhibition tasks independently capturing these subcomponents and subprocesses. Across all subcomponents, mutual activation was present in the right inferior frontal cortex (rIFC), pre-supplementary motor area (pre-SMA) and parietal regions. Interference inhibition revealed stronger activation in pre-motor and parietal regions. Action cancelation resulted in stronger activation in fronto-striatal regions. Our results show that all subcomponents share a common neural network and thus all constitute different subprocesses of response inhibition. Subprocesses, however, differ to the degree of regional involvement: interference inhibition relies more pronouncedly on a fronto-parietal-pre-motor network suggesting its close relation to response selection processes. Action cancelation, in turn, is more strongly associated with the fronto-striatal pathway implicating it as a late subcomponent of response inhibition. The new paradigm reliably captures three putatively subsequent subprocesses of response inhibition and might be a promising tool to differentially assess disturbed neural networks in disorders showing impulse control deficits.
Available online 14 September 2012
Gesehen am 12.08.2021